ANALISIS KEMAMPUAN KOGNITIF DAN KESULITAN BELAJAR SISWA MATERI SISTEM EKSKRESI DI SMA NEGERI 1 KARANG BARU - Fitri Amini; Mhd Yusuf Nasution; Mulkan Mulkan; Hartati Sugito (Universitas Negeri Medan, 2018)
This study aims to determine students' learning difficulties in the excretory system material in terms of cognitive aspects and learning indicators as well as the factors causing student learning difficulties in class XI IPA 1 Karang Baru at the year learning 2017/2018. The research design used is quantitative descriptive. Samples were taken by purposive sampling with a total of 95 students. The technique of data collection used diagnostic and questionnaire tests. The results showed that the percentage of students' learning difficulties from the highest to the lowest on the cognitive aspects they are C6, C4, C5, C3, C1 and C2 of 47.37%,for amount 46.5%, 46.00%, 39.61%, 34.74 % and 26.53%. The percentage of student learning difficulties based on indicators on the excretion system material are indicator 1 amount 28.95% medium category, indicator 2 amount 46.02% of very high category, indicator 3 amount 39.89% of high category and indicator 4 amount 42.32% of category high. Internal and external factors that cause the learning difficulties of learning difficulties from the highest to the lowest percentage are family (63,15%), interest (63,02%), school (63,00%), psychology (46,57%), teaching methods (45,21%), material (44,42%), motivation (44,21%), media (44,21%), teachers (44,12%) and health (44,03%).Keywords: Cognitive Aspects, Learning Indicators, Learning Difficulties, Excretion Systems